2009
DOI: 10.1111/j.1600-0722.2009.00622.x
|View full text |Cite
|
Sign up to set email alerts
|

Marginal accuracy of four‐unit zirconia fixed dental prostheses fabricated using different computer‐aided design/computer‐aided manufacturing systems

Abstract: Besides load-bearing capacity, marginal accuracy is a further crucial factor influencing the clinical long-term reliability of fixed dental prostheses (FDPs). The aim of this in vitro study was to evaluate the marginal fit of four-unit zirconia bridge frameworks fabricated using four different computer-aided design (CAD)/computer-aided manufacturing (CAM) systems. Ten frameworks were manufactured using each fabricating system. Three systems (inLab, Everest, Cercon) processed white-stage zirconia blanks, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
78
6
9

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(99 citation statements)
references
References 23 publications
5
78
6
9
Order By: Relevance
“…The choice of zirconia material in this study, i.e., HIP zirconia ceramic versus presintered zirconia ceramic, had no effect on strain development in the all-ceramic frameworks. This result contradicted a study conducted by Kohorst et al 25) and a review published by Abduo et al 2) , which claimed that restorations made from fully sintered zirconia showed better fitting accuracy.…”
Section: Strain Developmentcontrasting
confidence: 68%
See 2 more Smart Citations
“…The choice of zirconia material in this study, i.e., HIP zirconia ceramic versus presintered zirconia ceramic, had no effect on strain development in the all-ceramic frameworks. This result contradicted a study conducted by Kohorst et al 25) and a review published by Abduo et al 2) , which claimed that restorations made from fully sintered zirconia showed better fitting accuracy.…”
Section: Strain Developmentcontrasting
confidence: 68%
“…The contradicting results by Kohorst et al 25) as well as Vigolo and Fonzi 15) might be explained by the different study designs. In the current study, assessment was based on strain development, and hence fitting accuracy, using strain gage measurements 11) .…”
Section: Strain Developmentmentioning
confidence: 85%
See 1 more Smart Citation
“…The quality of the analysis is correlated to the number of measurement points [29]. Due to the necessary cutting process, there is a loss of information in the analogue twodimensional (2D) replica technique [20], and an evaluation based only on 2D is disadvantageous [30]. Analyses based on micro-computed tomography are also used [9,31].…”
Section: Introductionmentioning
confidence: 99%
“…Other investigations (Kohorst et al, 2009) in vitro assessed the marginal adjustment of four Zirconia bridges manufactured by 4 different systems of manufacturing assisted by computer (CAM). Three systems (inLab, Everest, Cercon) are presintered and had to be sintered to the final density after the milling, while with a system (Digident) the restorations were directly done with a material completely sintered.…”
Section: Discussionmentioning
confidence: 99%